Training of Farm Journalists : A Study of Needs and Preferences - Nain, Manjeet Singh; Trikha, R N (Indian Journal of Extension Education, 2022)
With the increased literacy, the print medium has assumed unprecedental role in technology transfer. Ever increasing number and circulation of farm periodicals from government and non government sector have made it an exter prise demanding professionalism and continuous training at all levels so that the participatory communication can be produced. In the backdrop of favourable attitude towards readers' context, situations, subject and farm literature, the informative and persuasive task of communication is likely to affect adversely. The study of perspective writers/contributors of farm periodicals revealed that majority of them were having no training in journalism, moderately favorable attitude towads farm periodicals and farmers and wrote articles for technology transfer. Most of the respondents were requiring training in almost all the sub areas of journalism with slight variations of preferences. The preferences on various facets of training in journalism such as duration, venue, size of group, theory - practical ration, resource person and time of year were also sought. The results of investigation suggest that the training of farm journalists can go a long way in accelerating the pace of rural development in many areas of human endeavor through print media.